Analisis Penyebab Terjadinya Kandas MV. Tanto Luas di Sungai Mahakam - Mochammad Firman; Firdaus Sitepu; Ardhiana Puspitacandri; A. A Ngurah Ade. D. P. Y (Pusat riset dan Inovasi Nasional, 2025)
Grounding incidents are among the most critical maritime accidents, posing significant threats to navigational safety, operational efficiency, and logistics continuity. This study aims to analyze the contributing factors behind the grounding of MV. Tanto Luas in the Mahakam River and to identify effective mitigation efforts. A descriptive qualitative approach was employed, with data collected through direct observation, interviews with ship crew, and documentation during onboard sea practice (PRALA). The findings reveal that the grounding incident was primarily caused by poor communication between MV. Tanto Luas and a tugboat, improper navigational decisions, and shallow, wave-affected waters. The Fishbone Diagram (Cause and Effect Diagram) method was used to systematically identify the root causes of the problem. Mitigation efforts included tank sounding, tidal monitoring, optimal use of navigational equipment, and improved inter-vessel coordination. The study concludes that grounding incidents can be prevented through enhanced communication, strict adherence to navigational procedures, and regular crew training. This research offers both practical and theoretical contributions to the enhancement of maritime safety in narrow waterways such as the Mahakam River.